1998
DOI: 10.3168/jds.s0022-0302(98)75586-9
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Development of Bovine Embryos Produced In Vitro by Addition of Cysteine and β-Mercaptoethanol to a Chemically Defined Culture System

Abstract: The aim of this research was to determine the effects of L-cysteine and beta-mercaptoethanol on the in vitro development of bovine embryos that had been produced in vitro. A 2 x 3 factorial arrangement of treatments was used to evaluate the effect of 0.63 or 6.9 microM L-cysteine and 0, 10, or 100 microM beta-mercaptoethanol on the development of bovine embryos in a chemically defined medium. Embryos containing 6 to 8 cells were randomly allocated to one of the six treatment combinations and were cultured for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…Following cryopreservation, oocytes and embryos become especially more sensitive to the oxidative stress, resulting in lipid peroxidation, membrane injury and structural destruction [3,23,24]. Low molecular-weight thiol compounds, such as βME, maintain the redox state of cells and protect them against the harmful effects of oxidative injuries and a number of studies have indicated the promoting effects of βME during in vitro embryo production [14][15][16][17][18]. However, data on the effect of βME are conflicting or inconsistent regarding favorable concentration of βME used in culture medium, and regarding the stage of IVP in which βME supplementation better supports embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following cryopreservation, oocytes and embryos become especially more sensitive to the oxidative stress, resulting in lipid peroxidation, membrane injury and structural destruction [3,23,24]. Low molecular-weight thiol compounds, such as βME, maintain the redox state of cells and protect them against the harmful effects of oxidative injuries and a number of studies have indicated the promoting effects of βME during in vitro embryo production [14][15][16][17][18]. However, data on the effect of βME are conflicting or inconsistent regarding favorable concentration of βME used in culture medium, and regarding the stage of IVP in which βME supplementation better supports embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Feugang et al [23] demonstrated no protective effect of βME on embryo development when added at 50 µM. In contrast, Geshi et al [16] showed that 10 µM βME in a co-culture system improves embryo development and Cammano et al [15] did not observed any difference between a low (10 µM) or high (100 µM) concentration of βME in development of resulting embryos. In addition, Geshi et al [16], Caamano et al [14] and Feuagang et al [23] reported better promoting effect of βME when added at 4-8 cell, 8-16 cell and beyond the morula stages, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations